ON PORTFOLIO OPTIMIZATION: ARE THERE FINANCIAL GAINS OF USING ALTERNATIVE COVARIANCE METHODS? - Saghir, Ahsen; Tirmizi, Syed Muhammad Ali; Mahmood, Ch Kamran; Mirza, Nauman Iqbal; Khan, Naeem (Humanities & Social Sciences Reviews, 2021)
Purpose: The study evaluates the performance of alternative variance-covariance estimators as a fundamental ingredient to portfolio optimization. Methodology: The study estimates eleven covariance matrices on the data of Pakistan stock exchange's non-financial sector firms covering the period from July 2006 to June 2020. The accuracy and efficiency of covariance estimators are assessed through two evaluation parameters: root mean square error and minimum variance portfolios (risk behavior). Main findings: Empirical findings based on evaluation parameters suggest that more complex covariance estimators in the equity market of Pakistan yield no additional financial gains than the equally weighted portfolio of estimators. Application of the study: As the estimation of the variance-covariance matrix is one of the essential elements of portfolio construction, this study guides investor(s) on selecting an appropriate covariance estimator among eleven estimators endorsed by literature. Novelty/ originality of the study: Based on detailed analysis, the study documents that investor(s) of the Pakistan stock exchange cannot gain any additional benefit from more complex and tricky methods of variance-covariance estimators compared to a portfolio of estimators for the non-financial sector. Investors are advised to consider the equally weighted portfolio of estimators when formulating their investment strategy.